Channel Hopping Sequences for Rendezvous Establishment in Cognitive Radio Sensor Networks - Widist Bekulu Tessema; Byeongung Kim; Junhyung Kim; Wooseong Cho; Kijun Han (International Journal of Distributed Sensor Networks)
In Cognitive Radio sensor networks, a pair of Cognitive Radio (CR) users wishing to communicate should first agree on a specific channel called control channel. Communication rendezvous is used to establish a control channel between CR users. Channel Hopping (CH) protocol is a sequence-based approach that provides an effective method for implementing rendezvous without relying on a Common Control Channel (CCC). In this approach, all CR users hop to the same rendezvous channel and hence this channel will serve as a control channel between them. In this paper, we propose two Channel Hopping Sequences (CHS) to establish a link in CR sensor networks with and without the assumption of global clock synchronization. Our schemes provide successful communication rendezvous within a bounded time interval. Theoretical analysis and simulation results showed that both schemes outperform the existing schemes used for similar purpose in terms of many performance criteria.